EXPERIENCE OF APPLICATION AND SAFETY ASSESSMENT OF THE 13-VALENT PNEUMOCOCCAL CONJUGATE VACCINE IN UNDER-5 CHILDREN - M. V. Fedoseenko; D. A. Novikova; N. E. Tkachenko; M. I. Broeva; T. A. Grechukha; A. G. Gaivoronskaya; V. V. Chernikov (Педиатрическая фармакология)
Compulsory use of the 7-valent pneumococcal conjugate vaccine in the framework of national pediatric immunization schedules of the developed countries resulted in significant decrease in the prevalence of the pneumococcal infections induced by the vaccinal serotypes. However, a growth in prevalence of the pneumonia and acute otitis media caused by non-vaccinal strains has also been observed. This required introduction of a new 13-valent pneumococcal conjugate vaccine with a wider range of pneumococcal population coverage. The experience of application accumulated in various countries (2010 onwards) and results of the authors’ observations indicate high safety of the 13-valent pneumococcal conjugate vaccine for both healthy under-5 children and patients with various medical issues. The article presents results of the 13-valent pneumococcal conjugate vaccination tolerance assessment. The study involved 110 children from 2 months to 5 years of age. In most cases immunization concurred with other pediatric vaccines. The incidence of local reactions in vaccinated children did not exceed 33%, of generalized reactions – 11%. The authors observed a comparable incidence of side reactions in both virtually healthy children and children with various medical issues.